Autopsy Study of thoraco-abdominal Injuries in Road Traffic Accident - Sirsat Kunal Bhimrao; Ambade Vipul N; Gilbe Pratik; Sharma Manu (Indian Journal of Forensic Medicine & Toxicology, 2021)
The present cross-sectional study was carried out in Apex Medical centre at Nagpur to determine the pattern of thoraco-abdominal injuries in road traffic accident. Two-wheeler riders were the commonest type of victims of thoraco-abdominal injuries followed by pedestrian. Motorised two-wheelers was the commonest type of victim’s vehicle in contrast to heavy motor vehicle (HMV- truck/ bus) as the commonest type of offending vehicle of thoracoabdominal injuries in road traffic accident. Thorax region was more commonly involved than abdominal region in thoraco-abdominal injuries with abrasion as the commonest type of external injury followed by contusion and laceration. Fracture of ribs was the commonest internal injury in thoracic region followed by injury to lungs in comparison to injury to liver in abdominal region. Laceration was the commonest type of injury in all thoracoabdominal organs except kidneys and bladder